Seeking Modernity in China's Name : Chinese Students in the United States, 1900-1927. - Ye, Weili (Stanford University Press, 2001)
"The students who came to the United States in the early twentieth century to become modern Chinese by studying at American universities played pivotal roles in Chinese intellectual, economic, and diplomatic life upon their return to China. These former students exemplified key aspects of Chinese "modernity," introducing new social customs, new kinds of interpersonal relationships, new ways of associating in groups, and a new way of life in general."